2022
DOI: 10.1002/cbdv.202100954
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Essential Oil and Hydrosol Composition of Sweet Wormwood (Artemisia annua L.) from Serbia

Abstract: The most abundant volatile compounds of sweet wormwood (Artemisia annua L.) essential oil were artemisia ketone (25.4 %) and trans‐caryophyllene (10.2 %), followed by 1,8‐cineole, camphor, germacrene D and β‐selinene. The major volatile compounds in the hydrosol were camphor (25.1 %), 1,8‐cineole (20.5 %) and artemisia ketone (10.7 %), followed by trans‐pinocarveol and yomogi alcohol. Tested essential oil was rich in oxygenated monoterpenes and sesquiterpene hydrocarbons, while the former were identified as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The phylogenetic cluster tree for DMEO was estimated and drawn using R software 4.0.3, as it is previously described for essential oil of white horehound [ 54 ], immortelle [ 55 ], hyssop [ 56 ], naked catmint [ 57 ], and sweet wormwood [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phylogenetic cluster tree for DMEO was estimated and drawn using R software 4.0.3, as it is previously described for essential oil of white horehound [ 54 ], immortelle [ 55 ], hyssop [ 56 ], naked catmint [ 57 ], and sweet wormwood [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gas chromatograph (Agilent 7890A) with two detectors, flame ionization (FID) and mass selective (Agilent 5975C) , and non-polar capillary column HP-5MS (30 m × 0.25 mm × 0.25 μm) were used for the analysis of DMEO and DMH. The operating conditions were the same as in our previous works [ 58 , 71 ]. Identification of the components was conducted according to their linear retention indices (RI), and comparison with mass spectral libraries (Adams ver.…”
Section: Methodsmentioning
confidence: 99%
“…The volatile fraction of the EO and HY were analyzed by GC/FID and GC-MS, as previously described by Aćimović et al [ 65 , 66 , 67 , 68 ]. The non-volatile compounds were analyzed in terms of total phenolic content by the spectrophotometrically microscale-adapted Folin–Ciocalteau method [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hydrolates, also known as floral aromatic waters as well as hydrosols, are produced by hydro-distillation or steam distillation [Aćimović et al 2020a]. During process, the fat-soluble and volatile compounds of the plants give rise to the essential oil, while the watersoluble components remain in the distilled water forming the hydrolate [Tavares et al 2022].…”
Section: Introductionmentioning
confidence: 99%
“…After years, the use of hydrolates has appreciably increased due to the rediscovery of their properties. Currently, many hydrolates are widely exploited in aromatherapy, cosmetic formulations, food industry and organic agriculture [Aćimović et al 2020a]. Several studies reported their antioxidant, anti-allergic, antiinflammatory antimicrobial and fungicidal properties as well as cytotoxic or anti-enzymatic activity [Boyraz & Ozcan 2006;Ko et al 2017;Shen et al 2017;D'Amato et al 2018;Mohamed Gameil et al 2019;Ha et al 2021;Pérez-Izquierdo et al 2022;Yu et al 2022].…”
Section: Introductionmentioning
confidence: 99%